(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
The article begins with a disquisition by John Bell on the superstitions that surrounded religious hand-bells in Ireland and Scotland, which survived into modern times. Bell’s notice introduces John Guthrie’s exhibition of The Guthrie Bell, which is illustrated in a plate. What follows is a history of the parish of Guthrie, which led them to the possession of such an important and sumptuously decorated bell, and a description of the decorations, which accrued in several stages.